Wpływ liberalizacji wymiany zagranicznej na stosunki handlowe na wybranych rynkach rolnych krajów wysoko rozwiniętych - Czyżewski, Andrzej; Poczta, Agnieszka (Impact of Agricultural Trade Liberalization on the Trade Relations in the Chosen Agricultural Markets of Highly-Developed Countries, 2006)
The main aim of this paper is to analyze the impact of Uruguay Round Agreement on Agriculture on the trade flows in chosen agricultural markets (wheat, beef and pork) of highly-developed countries. The special attention is paid to the issue of different treatment of developing and highly-developed countries. Reduction requirements for highly-developed countries have been more restrictive and their aim is to lower the share of highly-developed countries export share in total export. The results of the survey shows that URAA has have the biggest influence on wheat market. Although, the effect of URAA on the meat market has not been so strong, one can still see some improvement in amount of meat imported to highly-developed markets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 159-167